1996
DOI: 10.1523/jneurosci.16-21-06722.1996
|View full text |Cite
|
Sign up to set email alerts
|

Anion Conductance Behavior of the Glutamate Uptake Carrier in Salamander Retinal Glial Cells

Abstract: Glutamate uptake is driven by the cotransport of Na+ ions, the countertransport of K+ ions, and either the countertransport of OH- or the cotransport of H+ ions. In addition, activating glutamate uptake carriers has been shown to lead to activation of an anion conductance present in the carrier structure. Here we characterize the ion selectivity and gating of this anion conductance. The conductance is small with Cl- as the permeant anion, but it is large with NO3- or ClO4- present, undermining the earlier use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 30 publications
10
96
0
Order By: Relevance
“…Most kinetic models of the transport cycle describe the existence of an anion-conducting state after the substrate and cotransported ions have bound to the extracellular side of the transporter and before their translocation (14)(15)(16)(17)(18). In an alternative model the anion conducting state has been proposed to follow the translocation of substrate and cotransported ions (19). Our finding that modification impairs substrate translocation but not the anion conductance supports the existence of an anionconducting state before translocation.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Most kinetic models of the transport cycle describe the existence of an anion-conducting state after the substrate and cotransported ions have bound to the extracellular side of the transporter and before their translocation (14)(15)(16)(17)(18). In an alternative model the anion conducting state has been proposed to follow the translocation of substrate and cotransported ions (19). Our finding that modification impairs substrate translocation but not the anion conductance supports the existence of an anionconducting state before translocation.…”
Section: Discussionsupporting
confidence: 54%
“…In both heterologous and native systems expressing EAATs, reversal of the transmembrane electrochemical gradients for sodium and potassium ions leads to an outward flux of intracellular glutamate (3) and the activation of the transporterassociated anion conductance (19,21). To determine whether the modified carrier can catalyze reverse transport and͞or activate the anion conductance when ionic gradients are altered to favor substrate efflux, we applied a high potassium (40 mM), low sodium (60 mM) buffer to oocytes expressing the V449C or Cysless carriers.…”
Section: Functional Properties Of V449c Before and After Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that in addition to the uptake of glutamate, EAATs are coupled to an anion conductance that allows for larger currents when anions other than Cl Ϫ are used (Eliasof and Jahr, 1996;Billups et al, 1996). Therefore, we examined Mü ller cell responses to 1mM glutamate when extracellular Cl Ϫ was replaced by SCN Ϫ .…”
Section: Electrogenic Glutamate Transporter Activitymentioning
confidence: 99%
“…Since glutamate uptake is increased when pHi is more alkaline (Billups & Attwell, 1996), we investigated whether the potentiation of uptake by NHs was due to a change of pHi' Raising the Hepes concentration in the pipette from 5 to 71 mM, to clamp pHj at 7'0 more effectively, did not significantly alter the potentiation of the glutamate-evoked current (21 ± 2 %, n = 27). Potentiation of the glutamate-evoked current was smaller (7 ± 2 %, n = 19) but not abolished when the pH of the pipette solution was raised to 8'8 (a value at which the uptake current is not increased by further alkalinization; Billups & Attwell, 1996).…”
Section: Department Of Physiology University College London Gower Smentioning
confidence: 99%